Handbook of educational policy - Cizek, Gregory J. (Educational psychology., 1999)
This handbook examines policy questions on education in the USA. It reflects the premise that each member of society must take an active role in ensuring in children the cultivation of skills and responsibilities necessary for a free and virtuous social order.